2001
DOI: 10.1038/82931
|View full text |Cite
|
Sign up to set email alerts
|

Loudness constancy with varying sound source distance

Abstract: At a listener's ears, sound source power and sound source distance are confounded in measures of acoustic intensity, a physical property long thought to be the primary determinate of loudness. Although the relationship between sound source loudness and power is well known when source distance is fixed, relatively little is known about source loudness under conditions of varying distance. Here we show a robust loudness constancy, similar in many ways to visual size constancy, that results under distance-varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 28 publications
3
85
0
3
Order By: Relevance
“…The phenomenon by which loudness remains constant as distance from the sound source is changed is known as loudness constancy (see Zahorik and Wightman, 2001) because of its similarity to perceptual constancy (e.g., the perceived size of an object does not change when viewed at a distance; for a basic review of perceptual constancy see Goldstein, 2009). Zahorik and Wightman's (2001) experiment indicates that loudness constancy for distance is related to reverberant sound energy, which remains relatively constant with distance from a sound source in normally reverberant rooms.…”
Section: Possible Cues For Binaural Loudness Constancymentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon by which loudness remains constant as distance from the sound source is changed is known as loudness constancy (see Zahorik and Wightman, 2001) because of its similarity to perceptual constancy (e.g., the perceived size of an object does not change when viewed at a distance; for a basic review of perceptual constancy see Goldstein, 2009). Zahorik and Wightman's (2001) experiment indicates that loudness constancy for distance is related to reverberant sound energy, which remains relatively constant with distance from a sound source in normally reverberant rooms.…”
Section: Possible Cues For Binaural Loudness Constancymentioning
confidence: 99%
“…When stimulus presentation in experimental conditions approximate daily environments, such as in reverberant rooms with sighted listeners, the stimulus cues become more complex and interesting phenomena emerge. For example, a type of perceptual constancy occurs in which loudness remains relatively constant while sound source distance is varied (i.e., loudness constancy, see Zahorik and Wightman, 2001;Mohrmann, 1939). In fact, many factors influence the perception of loudness in daily environments.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall received stimulus intensity is an ambiguous distance cue (e.g., if the emitted stimulus intensity varies independently of the source distance), which can complicate studies on intensity vs. distance processing (23). Acoustically, for sources off the midline, it is impossible to fix the received stimulus intensity at both ears as distance varies, because the rate of change in intensity with distance is different at the two ears.…”
mentioning
confidence: 99%
“…They found out that for both frequencies and only for low-level stimuli, the higher was the ITD, the louder the sound was perceived. As high-level processes can affect loudness, like the loudness constancy occurring with the perception of distance (Zahorik and Wightman, 2001), the authors wondered if the loudness variations they observed were accounted for by the ITD itself or by the localization process. studied the loudness of tones comprising both ITD and interaural level differences (ILD) at the same time.…”
Section: B Influence Of Interaural Time Differences On Loudnessmentioning
confidence: 99%